Review. Impact of grazing on plant communities in forestry areas - Torrano, L.=700 1 Valderrabano, J.
(Es, En)
ilus., 112 ref.
Keywords: PASTOREO; DEGRADACION; VEGETACION; AGOTAMIENTO DE RECURSOS; ANATOMIA DE LA PLANTA; ESPAÑA; TOLERANCIA AL PASTOREO; ALTERACIONES MORFOLOGICAS; DINAMICA VEGETAL